2008
DOI: 10.1111/j.1742-1241.2008.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the orlistat on serum endotoxin lipopolysaccharide and adipocytokines in South Asian individuals with impaired glucose tolerance

Abstract: The increase in adiponectin levels in the orlistat group would suggest that orlistat may reduce the progression to type 2 diabetes in South Asian individuals by raising serum adiponectin. The finding that LPS levels are also reduced by orlistat and that this reduction correlates with the increase in adiponectin raises the possibility that the increase in adiponectin may be mediated via an effect on LPS levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 22 publications
9
34
0
1
Order By: Relevance
“…The decrease of TNF-a levels observed was in line with that reported by Kiortsis et al [55], but in contrast to that shown by Harrison et al [56] whereby TNF-a levels were significantly higher in the orlistat group compared with controls in overweight subjects with nonalcoholic steatohepatitis. On the other hand, our results were in line with those reported by Dixon et al [40], who reported that 1 year of dietary treatment with orlistat results in a greater increase in ADN, compared with dietary treatment alone in South Asian individuals with IGT.…”
Section: Control Groupsupporting
confidence: 95%
See 1 more Smart Citation
“…The decrease of TNF-a levels observed was in line with that reported by Kiortsis et al [55], but in contrast to that shown by Harrison et al [56] whereby TNF-a levels were significantly higher in the orlistat group compared with controls in overweight subjects with nonalcoholic steatohepatitis. On the other hand, our results were in line with those reported by Dixon et al [40], who reported that 1 year of dietary treatment with orlistat results in a greater increase in ADN, compared with dietary treatment alone in South Asian individuals with IGT.…”
Section: Control Groupsupporting
confidence: 95%
“…As with our study, Dixon et al reported an improvement of lipid profile, and especially triglycerides, after 1 year of dietary treatment with orlistat compared with dietary treatment alone in South Asian individuals with impaired glucose tolerance (IGT) [40]. Also Filippatos et al showed the positive effects of orlistat on lipid profile, both in monotherapy or in combination with other drugs such as fenofibrate [41,42] or ezetimibe [43], with combination therapy having a more favorable effect on improving metabolic parameters in overweight and obese patients compared with each monotherapy.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, fat deposition compromises intestinal permeability, liver function and the ability of Kuppfer cells to adsorb endotoxin [25], [26], whose circulating concentration is, therefore, increased. This in turn, mediates chronic low-grade of inflammation through the activation of TLR and the inflammosome pathway to exacerbate the insulin resistant state [27][30]. In agreement with these observation LPS plasma concentration was increased in obese individuals carrying the “at-risk” GTA genotype, suggesting a correlation between obesity and microbial translocation that could be responsible for the maintenance of the inflammatory state at systemic level.…”
Section: Discussionsupporting
confidence: 66%
“…Several teams have reported a relationship between impaired GI permeability and the translocation of live bacteria or LPS fragments into the bloodstream with the development of TD2 [178][179][180]. Translocation of bacterial fragments or whole bacteria into the systemic circulation leads to chronic immune activation and low-grade inflammation, which is the hallmark of metabolic endotoxemia as discussed previously.…”
Section: Increased Intestinal Permeability In Patients With Type 2 DImentioning
confidence: 93%